DETERMINAN FAKTOR STRES KELUARGA DALAM MERAWAT KLIEN GANGGUAN JIWA DI RUMAH - Dyah Widodo; Ganif Djuwadi (Poltekkes Kemenkes Malang, 2020)
Long-term mental disorder treatment, various problems of client behavior and negative views of the community about mental disorders can result in high-stress levels for a family. The general objective of the study analyzes the determinants of the most dominant factors related to family stress in caring for clients with mental disorders at home. The correlation research design includes a sample of 200 people living in East Java, all of whom live with a person suffering from a mental disorder. A consecutive sampling technique was used to create this sample. The data was collected in the Poly Mental Health unit of a Mental Hospital in dr. Radjiman Wediodiningrat Lawang East Java - Indonesia. The research instrument used to collect the data was a questionnaire that had been tested for its validity and reliability. The Data analysis used descriptive and inferential statistical testing. The results of study obtained were as follows: 1. There was a very weak relationship between education and family stress caused by caring for home psychiatric clients, with p is 0.041 and r is 0.145; 2. There was a relationship between the duration of clients experiencing mental disorders and family stress caused by treating mental disorders at home. The p value is 0.026 and r is -0.158, meaning the strength of the relationship was very weak. i.e. the longer the client has had a mental disorder, the lower the stress level experienced by the family; meaning that the strength of the relationship is very weak in the opposite direction, ie the longer the client experiences a mental disorder the lower the stress level experienced by family; 3. Gender and age factors have nothing to do with family stress in caring for clients with mental disorders at home; 4. The most dominant factor related to family stress in caring for mental disorders clients at home is the length of time clients experience mental disorders. It is recommended that actions be taken to anticipate and deal with stress in families that have family members with mental disorders. Keywords: determinant factors, family stress, mental disorder care